Liquid Chromatography (LC) troubleshooting guide - Odenkirk, Melanie T; Jones, Rachel; Prenni, Jessica; Brinkley, Sarah (2025)
This Liquid Chromatography (LC) Troubleshooting Guide provides a structured, step-by-step framework to identify and resolve common performance issues encountered during LC analysis. Organized into three interactive flow charts, the guide begins with observable problems—irregular LC pressure, inconsistent retention times, and unusual pressure traces—and leads users through a series of diagnostic questions toward one of six targeted solutions. Each solution addresses common causes such as leaks, clogged components, worn consumables, or sample matrix effects, and includes actionable maintenance recommendations. The guide is designed for both novice and experienced users, with direct links to specific troubleshooting pathways and supplementary notes for advanced guidance. If a specific issue is not resolved within the guide, users are encouraged to reach out to the PTFI Onboarding Technical Experts for additional support.